Sources of the Paleomagnetic Signal in Iron-Rich Marine Sedimentary Rocks; Doklady Chemistry; Vol. 486, No. 1 - Rudmin M. A. Maksim Andreevich; Mazurov A. K. Aleksey Karpovich; Sergienko V. I. Valentin; Savichev O. G. Oleg Gennadievich; Semiletov I. P. Igor Petrovich (2019, 2019)
Title screen